2000
DOI: 10.1126/science.287.5455.989
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and Novelty in the Evolution of Cell Adhesion and Extracellular Matrix Genes

Abstract: New proteins and modules have been invented throughout evolution. Gene "birth dates" in Caenorhabditis elegans range from the origins of cellular life through adaptation to a soil habitat. Possibly half are "metazoan" genes, having arisen sometime between the yeast-metazoan and nematode-chordate separations. These include basement membrane and cell adhesion molecules implicated in tissue organization. By contrast, epithelial surfaces facing the environment have specialized components invented within the nemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
169
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(181 citation statements)
references
References 68 publications
1
169
0
3
Order By: Relevance
“…Among them are the basement membrane collagens IV, XV, and XVIII, which possess C-terminal globular domains (NC1) that recently have been implicated in angiogenesis control as reviewed in (7 ). Homologs of these collagens have been also identified in C. elegans (8) and Drosophila, indicating ancient functions not necessarily related to vessel growth. Collagens XV and XVIII are classified together as the subfamily of multiplexins: they share a central collagen triple-helix with typical Gly-X-Y sequence repeats that is frequently interrupted by short nontriplet sequences (Fig.…”
Section: Collagens XV and Xviiimentioning
confidence: 99%
“…Among them are the basement membrane collagens IV, XV, and XVIII, which possess C-terminal globular domains (NC1) that recently have been implicated in angiogenesis control as reviewed in (7 ). Homologs of these collagens have been also identified in C. elegans (8) and Drosophila, indicating ancient functions not necessarily related to vessel growth. Collagens XV and XVIII are classified together as the subfamily of multiplexins: they share a central collagen triple-helix with typical Gly-X-Y sequence repeats that is frequently interrupted by short nontriplet sequences (Fig.…”
Section: Collagens XV and Xviiimentioning
confidence: 99%
“…Individual cell adhesion and ECM-associated domains in the M. brevicollis genome often occur in unique arrangements, and clear orthologues of specific metazoan adhesion proteins are rarely found. Although the domains associated with metazoan adhesion and ECM proteins were present in the ancestor of choanoflagellates and metazoans, the canonical metazoan adhesion protein architectures 35 …”
Section: Extracellular-matrix-associated Protein Domainsmentioning
confidence: 99%
“…Gene structure and intron evolution The ,41.6 megabase (Mb) M. brevicollis genome contains approximately 9,200 genes (Supplementary Notes 1 and 2) and is comparable in size to the genomes of filamentous fungi (,30-40 Mb) and other free-living unicellular eukaryotes (for example, small diatoms at , [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and ichthyosporeans at ,20-25 Mb 21 ). Metazoan genomes are typically larger, with few exceptions 22 .…”
mentioning
confidence: 99%
“…A minimally immunogenic scaffold with a native intact structure for new tissue regeneration may be produced in that the ECM proteins are the most conserved proteins. 2 The initial applications of the decellularization matrix have been demonstrated only for the hollow organs or thin layer of tissues, such as bladder, artery, esophagus, trachea, and skin. [3][4][5][6][7] Ott et al reported that they constructed a heart by using a rat's decellularized heart scaffold.…”
Section: Introductionmentioning
confidence: 99%